2020
DOI: 10.1364/ol.410387
|View full text |Cite
|
Sign up to set email alerts
|

Hollow-core resonator fiber optic gyroscope using nodeless anti-resonant fiber

Abstract: Resonator Fiber-Optic Gyroscope (RFOG) performance has hitherto been limited by non-linearity, modal impurity, and backscattering in the sensing fibers. The use of hollow-core fiber (HCF) effectively reduces non-linearity, but the complex interplay among glass and air-guided modes in conventional HCF technologies can severely exacerbate RFOG instability. By employing high-performance nested anti-resonant nodeless fiber, we demonstrate long-term stability in a hollow-fiber RFOG of 0.05 deg/hr, nearing the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(23 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…The applications depicted in Figure 5a-h are all employed in fluidic detection, including gas and liquid. While in Figure 5i, HC-NANF is wound into a coil to be integrated into a resonator fiber optic gyroscope [66]. This structure not only breaks through the limitation of nonlinear influence, but also considerably improves spatial mode purity.…”
Section: Versatile Platform Based Sensing Applicationsmentioning
confidence: 99%
“…The applications depicted in Figure 5a-h are all employed in fluidic detection, including gas and liquid. While in Figure 5i, HC-NANF is wound into a coil to be integrated into a resonator fiber optic gyroscope [66]. This structure not only breaks through the limitation of nonlinear influence, but also considerably improves spatial mode purity.…”
Section: Versatile Platform Based Sensing Applicationsmentioning
confidence: 99%
“…Problems arise from nonlinearity, modal impurity and backscattering in the fibres and although the use of hollow-core fibre (HCF) effectively reduces nonlinearity, the complex interaction between glass and air-guided modes can create significant FOG instability. Now, work by Honeywell and Southampton University (Sanders et al , 2021), employs an entirely new type of HCF, the nested antiresonant nodeless fibre (NANF). These exhibit even lower nonlinear effects than other HCFs and also have low optical attenuation, which improves the quality of the resonator as the light maintains its intensity over longer propagation lengths.…”
Section: Navigation Technologiesmentioning
confidence: 99%
“…Besides, splices or other polarizationdependent devices add undesirable loss and backscatter to the FRR. The emergence of hollow-core photonic-crystal fiber (HCPCF) offers a novel approach to reduce the Kerreffect-induced drift [17,18] and polarization errors [19,20]. However, other experimental results indicated that the backscattering coefficient of some commercial HCPCFs are two orders of magnitude lager than the typical backscattering coefficient observed for SMF-28 fiber [21,22], which means the RFOG with a single HCPCF ring resonator may increase the Rayleigh backscattering noise.…”
Section: Introductionmentioning
confidence: 99%